Analisis Laporan Keuangan pada Akad Pembiayaan Murabahah Berdasarkan PSAK 102: Studi Kasus Baitul Maal Tamwil (BMT) Syariah Riyal (BSR) Kabupaten Bekasi - Intishar, Fathonah; Bianda, Ryan; Muti, Ahmad (Ikatan Da'i Indonesia, 2024)
This study aims to analyze the financial statements of murabahah financing contracts based on PSAK 102 with a case study on BMT Syariah Riyal Bekasi Regency. This study is a qualitative research with data collection techniques such as interviews, observations and documentation. This study aims to analyze the financial statements on the murabahah financing contract at BMT Syariah Riyal. However, in fact, Islamic banking and Islamic financial institutions in writing financial reports on murabahah contracts have not fully complied with PSAK 102 which explains murabahah contracts. This study provides empirical evidence in understanding the writing of financial statements of murabahah financing contracts based on PSAK 102.